Roles of osteoprotegerin in endocrine and metabolic disorders through receptor activator of nuclear factor kappa-B ligand/receptor activator of nuclear factor kappa-B signaling - Zhang, Luodan; Zeng, Fa; Jiang, Minmin; Han, Maozhen; Huang, Binbin (Frontiers in Cell and Developmental Biology, 2022)
Abstract: Endocrine and metabolic diseases show increasing incidence and high treatment costs worldwide. Due to the complexity of their etiology and mechanism, therapeutic strategies are still lacking. Osteoprotegerin (OPG), a member of the tumor necrosis factor receptor superfamily, appears to be a potential candidate for the treatment of these diseases. Studies based on clinical analysis and rodent animal models reveal the roles of OPG in various endocrine and metabolic processes or disorders, such as bone remodeling, vascular calcification and β-cell proliferation, through receptor activator of nuclear factor kappa-B ligand (RANKL) and receptor activator of NF-κB (RANK). Thus, in this review, we mainly focus on relevant diseases, including osteoporosis, cardiovascular disease (CVD), diabetes and gestational diabetes mellitus (GDM), to summarize the effects of the RANKL/RANK/OPG system in endocrine and metabolic tissues and diseases, thereby providing comprehensive insight into OPG as a potential drug for endocrine and metabolic diseases.